2011
DOI: 10.1118/1.3597568
|View full text |Cite
|
Sign up to set email alerts
|

The invariance of the total direct DNA strand break yield

Abstract: The SSB generation process is homogeneous and independent of the LET of the particles involved, at least within the proton and alpha particle energy range here studied. The target-hit probability is only determined by the ratio between the total volume occupied by targets and that of the ROI where the radiation deposits its energy. The maximum separation distance between two adjacent SSBs to produce a DSB is the parameter that breaks the homogeneity of the target-hit process, making the DSB production process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 24 publications
8
44
1
Order By: Relevance
“…This simplified nucleus was irradiated with incident protons and the authors confirmed the weak dependence of the total strand break yields with incident particle LET, as already observed in [50]. The DSB yield was found to be strongly dependent on LET.…”
Section: The Cylinder Volumes Approachsupporting
confidence: 78%
See 3 more Smart Citations
“…This simplified nucleus was irradiated with incident protons and the authors confirmed the weak dependence of the total strand break yields with incident particle LET, as already observed in [50]. The DSB yield was found to be strongly dependent on LET.…”
Section: The Cylinder Volumes Approachsupporting
confidence: 78%
“…Irradiating a total of 900 fragments of such chromatin fibres with incident protons and alpha particles in the 0.5 -10 MeV range, the authors could demonstrate that the total strand break yield and the number of energy deposition events required to reach a certain absorbed dose were found nearly independent of the type and energy of the incident ion. The SSB generation process was found to be homogeneous, depending neither on the structure of the DNA nor on the LET of the particles involved, while the DSB yield was found strongly dependent on the LET of the incident radiation [50].…”
Section: The Cylinder Volumes Approachmentioning
confidence: 85%
See 2 more Smart Citations
“…A variety of applications based on GEANT4-DNA processes and models allow the study of elementary energy deposition patterns at the sub-cellular scale. For example, the comparison of dose point kernels [114], S-values [115], radial doses [116], cluster patterns for ions with the same LET [117], the effect of a magnetic field on electron track structures [118], and the modeling of direct DNA damage [119][120][121][122] have so far been explored utilizing these tools. They even provide a framework for the future study of non-targeted biological effects [123], extending further the first applications of GEANT4 electromagnetic physics at the physics-biology frontier [124][125][126][127][128][129][130].…”
Section: Geant4-dna Physics Modelsmentioning
confidence: 99%